Alternate mRNA splicing is required for synthesis of adeno-associated virus VP1 capsid protein. - Trempe, J P (1988)
Fine-structure mapping of the capsid-specific mRNAs from adeno-associated virus (AAV) revealed an alternate splicing pattern in these RNAs. S1 nuclease and primer extension analyses showed that splicing of these mRNAs occurs at acceptor sites at nucleotide 2228 (major splice) or 2201 (minor splice). Both splice acceptors were ligated to the same 55-nucleotide leader in mature mRNAs. Both species were present in equal amounts in mRNA derived from AAV plasmid-transfected cells. However, when adenovirus infection accompanied the DNA transfection, the major splice predominated over the minor splice. Using cDNA clones of both the major and minor spliced mRNAs, we demonstrated that the largest AAV capsid protein, VP1, was derived from the minor spliced mRNA. The other capsid proteins, VP2 and VP3, came predominantly from the major spliced mRNA. These results, which describe the previously undetected minor splice, provide a mechanism for the production of all three AAV virion proteins.